Performing unbelonging in court: observations from a transnational corporate bribery trial - a dramaturgical approach - Schoultz, Isabel (Crime, law and social change, 2022)
This article presents a study of the theatrical performance in court in a high-profile transnational corporate bribery case. Data gathered from observations in court were supplemented with interviews with the defense teams and the presiding judge. The paper’s objective is to demonstrate how the defendants performed unbelonging in court via the interactions between the different ‘teams’ in the courtroom; the defense, the prosecutors, the judges, and the company Telia. The analysis draws on Goffman’s theater analogy and his understandings of performance and self-presentation. The authors introduce the concept of ‘performing unbelonging in court’ and show how the defendants performed unbelonging via an indirect expression of status and standing. The authors further analyze the defense teams’ framing of the case, including the framing of the defendants as being scapegoated by the corporation, and of the prosecution as being unfair and illegitimate, which also contributes to the performance of unbelonging in court. The complexity and ambiguity of a transnational corporate bribery case permeated the interactions during the trial; however, at the end of the article, the authors discuss how knowledge from this case is transferable to other crime types or legal cultures.